2018
DOI: 10.1111/imb.12517
|View full text |Cite
|
Sign up to set email alerts
|

The transformer2 gene of the pumpkin fruit fly, Bactrocera tau (Walker), functions in sex determination, male fertility and testis development

Abstract: The insect transformer2 (tra2) gene has a prevalent role in cooperating with the sex-determining gene transformer (tra) to direct female differentiation. Here, we report the identification and characterization of Btau-tra2, the tra2 orthologue of the pumpkin fruit fly, Bactrocera tau, an invasive agricultural pest. The Btau-tra2 gene produces three transcript variants. However, only two transcripts can be examined; one is present at all developmental stages in the soma and germline of both sexes and the other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…In tephritid fruit flies, mRNA variants of Tra-2 have been reported. For example, three mRNA variants of Tra-2 have been identified in Z. tau, of which at least one is expressed in both sexes and the other is specific to the embryo or germline [21]. Although Zs-Tra2 mRNA variants were not assessed in our current study, its expression profile in males suggested the presence of variants of the Zs-Tra2 transcript.…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations
“…In tephritid fruit flies, mRNA variants of Tra-2 have been reported. For example, three mRNA variants of Tra-2 have been identified in Z. tau, of which at least one is expressed in both sexes and the other is specific to the embryo or germline [21]. Although Zs-Tra2 mRNA variants were not assessed in our current study, its expression profile in males suggested the presence of variants of the Zs-Tra2 transcript.…”
Section: Discussionmentioning
confidence: 66%
“…In B. dorsalis, nearly 100% males were obtained with embryonic RNAi against Tra-2 [20]. In Z. tau, dsRNA injection to embryo has produced 72.4% males while the control has produced only 38.6% males [21]. This indicated an increase of 187.6% in male production.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The presence in unfertilized eggs of only the Btau-dsx F transcript sug-gests that Btau-dsx pre-mRNA may be a maternal substrate transferred to the eggs during oogenesis. Since we also detected the maternal transformer female-specifi c (Btautra F ) transcript (our unpublished data) and the maternal transformer2 (Btau-tra2) transcript (Thongsaiklaing et al, 2018) in early laid unfertilized and fertilized eggs, it is likely that in B. tau female embryos and in unfertilized eggs, the maternal Btau-dsx pre-mRNAs may be spliced into the female mode upon activation of the maternal Btau-TRA/Btau-TRA2 protein complex. In early fertilized eggs, the Btau-dsx M1 transcript was also detected, albeit at low levels, indicating that the Btau-dsx M1 transcript may exist only in male embryos.…”
Section: Expression Of Btau-dsxmentioning
confidence: 74%